AB1462-HPR Activity limitations and perceived health-related quality of life in people with inclusion body myositis – a cross-sectional study. (12th June 2018) - Regardt, M; Eriksson, B.; Christopher-Stine, L.
Abstract : Background: Inclusion body myositis (IBM) is a slowly progressive inflammatory myopathy with muscle weakness around thighs, knees and finger flexion muscles. Most people are 50 years or older at onset and there are more men than women with ratio of 2–3: 1. The diagnosis leads to activity limitations in daily life. Objectives: The aim of this study was to describe how individuals with IBM describe their activity limitation and how they estimate their perceived health-related quality of life as well as to describe the correlation between activity limitation and experienced health-related quality of life. Methods: A quantitative cross-sectional study involving a total of 29 people with IBM participated. Data collection was performed in Stockholm Sweden. The Myositis Activities Profile (MAP) were used to measure activity limitation and the Short Form-36 (SF-36) were used to measure experienced health-related quality of life. Results: Activity limitations were estimated from no difficulty to impossible to do. The activity with the highest value (very difficult) was movement. There was a significant difference between individuals with IBM and Swedish normative references measured with SF-36 in physical function, physical role function, general health and social function (p≤0.01). There were high correlations between SF-36 physical and social function with MAP's movement, household activities, social activity, work/school and leisure (−0.872 ≥rs≤ -0.702; p≤0.001). Conclusions: Participants estimated activity limitations in many areas, of which movement was estimated as very difficult. The study demonstrated correlation between activity limitations and the experience of impaired health-related quality of life. In order to make positive impact on the health-related quality of life, it is important to focus on social areas such as family, friends and leisure activities, as well as optimising everyday living with proper mobility tools. Acknowledgements: We would like to thank all the participant for taking time to be part of this study. We acknowledge The Myositis Association for making this study possible with a fellowship grant. Disclosure of Interest: None declared